Technological surveillance of aromatic species: from research to the consolidation of the productive chain in Colombia (2017)
The sector of aromatic, medicinal and seasoning herbs brings together a wide variety of native and introduced species with agroindustrial potential. In order to contribute to the technological assessment of the sector in Colombia and provide elements of strategic planning towards higher levels of development and internationalization. We prioritized certain aromatic species in this article and a technological surveillance was made during 2004-2014. A searching scientific articles and patents was made in eight national, iberoamericanand worldwide databases according prioritized issues. Data processing was performed using Microsoft Excel, EndNote, Vantage Point (2014) Thomson Data Analyzer programs. At National level, the planting material and breeding has been the main researched topic; whereas in iberoamerica and the world was biocidal effect. The leading countries in research on the monitored aromatic plants were Brazil, Colombia and Cuba. Internationally, the scientific leaders according to PubMed and Scopus were India, USA, Brazil and Colombia. The global trend in the field of patents has increased, whose main focus is: “Current needs of life”. This technological surveillance gives an overview of developments and trends in research and technological development in different subject areas within the aromatic plants, besides identifying possible allied research and the scientific production trends over time.